Den engasjerte eleven Undrende, utforskende og aktiviserende undervisning i skolen - Kathrine Hundal, Anne (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Passion for learning has become a key concept in the politics of education. We want to establish schools where students are motivated, enthusiastic and feel a desire to learn. To achieve this on behalf of all students, an emphasis has to be placed on schools where students can experience mastery on the basis of their individual qualifications. Variation in instruction is crucial for students to feel mastery and thus the desire to learn more. A significant springboard for increased desire to learn can be found in enthusiasm. The enthusiastic teacher often receives a good deal of deserved attention. Only when students become enthusiastic about learning can beneficial learning outcomes arise. In The Enthusiastic Student the authors demonstrate how instruction that incorporates wonder, investigation and activation can lead to more enthusiastic students. This anthology includes 12 peer-reviewed chapters written by authors who lecture in a broad range of subjects at Nord University's Faculty of Education and Arts. The book is in two parts. The first part opens with introductory chapters that explain the concepts of wondering, investigative and activating instruction, and what distinguishes these three approaches from each other. In addition, the basic principles and overall perspective behind the choices of instructional form and the relationship to the student which will influence the learning outcomes in each case, are also explained. This is essential information when it comes to evaluating teaching practices: Why did the plan function well? Why did it not? Part two of the book presents the different wondering, investigative and activating working forms. Some of the methods are presented within the context of one or two subjects; other methods are presented more generally. In these chapters, the reader will find examples that illustrate motivation theory, more insight into the value of interdisciplinary work, and possible effects we can achieve with teaching activity that is not necessarily out after that one right answer. This anthology will be of interest to students and teachers seeking to create more enthusiasm among students in the teaching situation."